Biliary transpapillary endoscopic balloon dilation for treating choledocholithiasis - Daniel, Lubia B. (2017)
Objective: To evaluate the efficacy and safety of transpapillary papilloplasty in patients with choledocholithiasis. Materials and methods: All endoscopic retrograde cholangiopancreatography (ERCP) procedures performed at Hospital Ana Costa, in the city of Santos, Brazil, over the last five years were retrospectively evaluated using the hospital’s information database. The success of the procedure and complications due to residual calculi, pancreatitis, bleeding and perforation were evaluated. Results: From January 2010 to May 2014, 1860 ERCP procedures were performed. Fifty-five patients were evaluated here. Their ages ranged from 12 to 98 years (mean, 66.3; standard deviation, 19.34; median, 71). Thirty-two patients (58.2%) were women. Sixteen (29.1%) presented giant choledocholithiasis, with calculi larger than 12 mm. Twenty-seven (49.1%) had multiple choledocholithiasis. Conclusion: In view of the therapeutic efficacy and low complication rate among our patients, we can conclude that endoscopic papilloplasty is a safe and effective method for endoscopic treatment of choledocolithiasis in selected cases.